2021
DOI: 10.1111/psyp.13956
|View full text |Cite
|
Sign up to set email alerts
|

Impaired differential learning of fear versus safety signs in obsessive‐compulsive disorder

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…extent than do non-anxious control participants, owing to heightened fear responses to the safety cue in those with an anxiety disorder [66][67][68][69] . Despite the evidence confirming the results of the meta-analysis discussed above 51 , a few studies found lower skin conductance responses to the threat cue in individuals with PTSD and obsessive-compulsive disorder than in controls 70,71 . Although those observations might be consistent with a deficit in differentiating threat from safety cues, they deviate from the conclusion of the meta-analysis that there are differences in differential responding but generally not in threat cue responding between individuals with and without anxiety disorder.…”
Section: Extinction Generalization and Avoidancementioning
confidence: 75%
“…extent than do non-anxious control participants, owing to heightened fear responses to the safety cue in those with an anxiety disorder [66][67][68][69] . Despite the evidence confirming the results of the meta-analysis discussed above 51 , a few studies found lower skin conductance responses to the threat cue in individuals with PTSD and obsessive-compulsive disorder than in controls 70,71 . Although those observations might be consistent with a deficit in differentiating threat from safety cues, they deviate from the conclusion of the meta-analysis that there are differences in differential responding but generally not in threat cue responding between individuals with and without anxiety disorder.…”
Section: Extinction Generalization and Avoidancementioning
confidence: 75%
“…Further, some studies administer self-report measures designed explicitly to test components of conditioning models (e.g., expectation violation; Elsner et al, 2022), but do not assess objective in vivo measures of conditioned responding (e.g., psychophysiology). If intervention scientists seek to directly test temporal dynamics of candidate conditioning-related mechanisms of change during a treatment study, the reliability of conditioning tasks on the scale of weeks must be established.…”
Section: Introductionmentioning
confidence: 99%
“…These relatively shorter test–retest intervals are important, as many exposure therapy studies assess changes in symptoms and related psychological variables (e.g., treatment mediators) every week or biweekly (e.g., Kothgassner et al, 2019; Mataix‐Cols et al, 2017). Further, some studies administer self‐report measures designed explicitly to test components of conditioning models (e.g., expectation violation; Elsner et al, 2022), but do not assess objective in vivo measures of conditioned responding (e.g., psychophysiology). If intervention scientists seek to directly test temporal dynamics of candidate conditioning‐related mechanisms of change during a treatment study, the reliability of conditioning tasks on the scale of weeks must be established.…”
Section: Introductionmentioning
confidence: 99%